A comprehensive review of the development of green extraction methods and encapsulation of theobromine from cocoa bean shells for nutraceutical applications - Alvarez-Yanamango, Erick (2025)
Cocoa bean shells (CBS) represent up to 20% of the waste from roasted beans in emerging countries, such as Peru, one of the leading producers of fine-aroma cocoa (Theobroma cacao L.) in the world. Due to the high phenolic and theobromine concentrations in agricultural residues such as cocoa bean shells (CBS), multidisciplinary research is focused on optimizing the extraction, characterization, and evaluation of phenolic compounds present in CBS. To provide a complete guide for the extraction of theobromine from CBS, we present here the main methods of extraction and stabilization (encapsulation) of theobromine present in CBS, moving from conventional techniques to others considered “green,” such as ultrasound-assisted extraction (UAE), microwave-assisted extraction (MAE), supercritical fluid extraction (SFE), pressurized liquid extraction (PLE), even deep eutectic solvent extraction (DES), hydrodynamic cavitation reactors (HCR), pulsed electric field (PEF), and high-voltage electric discharge extraction (HVED), pressurized hot water extraction (PHWE) and subcritical water extraction (SCE), among others. Here, the significant increase in theobromine concentration of the extracts is highlighted, as well as the importance of microencapsulation and nanoencapsulation in protecting their bioactivity. The UAE and MAE methods are more effective for theobromine extraction, respectively. On the other hand, encapsulations have been evaluated primarily with maltodextrin mixed with gum Arabic, chitosan, and whey protein by spray drying or freeze-drying. It is concluded that obtaining a nutraceutical product from CBS in a sustainable circular agricultural economy requires optimizing scalable green extraction processes, such as US, and exploring new encapsulated materials and their mixtures to stabilize bioactive compounds, taking advantage of synergistic protection effects.